Women in formal corporate networks: an organisational citizenship perspective. - Singh, Val; Vinnicombe, Susan; Kumra, Savita (Emerald Group Publishing Limited, 2006)
To investigate women's corporate networks, and the reported benefits for the women and their employers. To gain insight into the motivation for these voluntary activities, by drawing on organisational citizenship theory.
Keywords: Networking; Organisational behaviour; Volunteering; Women; Women executives